The Influence Of Price, Product Quality, And Promotion On Purchasing Decisions On Toast Store In Tangerang City - Saddha Budianto Kirtileka; Pujiarti Pujiarti; Andy Andy (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
Many stores provide products the various and varied ways of preparing bread make many shops sell a variety of processed bread. One example is the processing of bread by baking. Toast is a processed bread that contains meat and vegetables with various processed sauces, and a processed bread that is served with sweet toppings and topped with various flavors that are then baked. The author sees many stores that provide processed bread products that are different from each other that vary. With so many shops offering a variety of processed toasts, it will inevitably lead to competition, In this study, the type of the research conducted is descriptive research. Descriptive research analyzes data systematically. The conclusion that produced is not general. The type of descriptive research is research survey. This study sought to determine how pricing, product quality, and promotion affected consumers’ decisions to buy toast at Tangerang City’s toast shops, researchers took three examples of toast shops in Tangerang City, namely Tokyo Cheese Toast, Roti Bakar 88, and Jiwa Toast. In studies that have been carried out, it shows that adjusted R Square has a value of 0.827. From the value obtained, it is stated that the price, product quality, and promotion of purchasing decisions have an influence with a value of 82.7% while the rest  are other influencing factors. Based on t test research, it shows that the price has a value of 11,949 > 1,657. With a value of Sig. known 0.000 < 0.05. The product quality variable has a value of 20.494 > 1.657. With a Sig value of 0.000 < 0.05. The promotion variable has a value of 17.783 > 1.657. With a Sig value.  0.000 < 0.05. The fact that Ha is accepted suggests that independent variables influence in part purchasing decisions.